Development of a Low-Cost Integrated Non-Invasive Glucose-Hemoglobin Meter - Akpan, Vincent Andrew; Abodunrin, Bolaji Adewale (Journal Electrical and Computer Experiences, 2025)
Diabetes and Anemia are amongst the deadliest diseases known worldwide. To prevent further complications due to these diseases, it is vital to regularly monitor the blood glucose and hemoglobin levels. Conventional ways to measure these blood parameters are invasive, which involves finger puncturing. This method is painful and increases risk of infection. Over a long term, the invasive method results in damage of finger tissues. As an alternative, the non-invasive method can be used which facilitates frequent testing, relieves pain and discomfort caused by frequent finger pricks. This paper presents the development of a low-cost integrated non-invasive glucose-hemoglobin (NIGH) meter for the simultaneous measurement and monitoring glucose and hemoglobin level. The developed low-cost integrated NIGH meter is calibrated firstly using mathematical method and secondly against standard invasive methods of glucose and hemoglobin measurement. The low-cost integrated NIGH meter provides a user-friendly interface, displaying simultaneous real-time glucose and hemoglobin measurements. The results from the numerical analysis and Bland-Altman graphs of the developed NIGH meter shows good agreements with the standard invasive methods for the glucose and hemoglobin measurements; and indicates that the developed low-cost integrated NIGH meter can be deployed and use at home, clinical environments, hospitals and rural areas.